2017
DOI: 10.1016/j.gaitpost.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Gait deficiencies associated with peripheral artery disease are different than chronic obstructive pulmonary disease

Abstract: Objective Previous studies have indicated that patients with peripheral artery disease (PAD), display significant differences in their kinetic and kinematic gait characteristics when compared to healthy, aged-matched controls. The ability of patients with chronic obstructive pulmonary disease (COPD) to ambulate is also limited. These limitations are likely due to pathology-driven muscle morphology and physiology alterations establish in PAD and COP, respectively. Gait changes in PAD were compared to gait chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…While McCamley et al [25] did not find any significant difference, Yentes et al [22] observed an altered pattern at the ankle level, after correcting for covariates of age, gender and smoking history. In particular, they measured an increased peak ankle power absorption at mid-stance and a lack of increase in peak ankle dorsiflexion moment in fatigued conditions with respect to controls.…”
Section: Summary Of Evidencementioning
confidence: 89%
See 4 more Smart Citations
“…While McCamley et al [25] did not find any significant difference, Yentes et al [22] observed an altered pattern at the ankle level, after correcting for covariates of age, gender and smoking history. In particular, they measured an increased peak ankle power absorption at mid-stance and a lack of increase in peak ankle dorsiflexion moment in fatigued conditions with respect to controls.…”
Section: Summary Of Evidencementioning
confidence: 89%
“…Yentes et al [23] noticed a consistent (−15%) whilst not significant (p = 0.06, t-test) reduction in gait speed. McCamley et al [25] and Yentes et al [22] did not find significant differences between groups, since they matched patients and controls in terms of walking speed, either a-priori or by covariate analysis. In addition, patients with COPD generally tend to reduce their stride (and step) length and cadence [12,23,26,27].…”
Section: Summary Of Evidencementioning
confidence: 97%
See 3 more Smart Citations